Thanatin targets the intermembrane protein complex required for lipopolysaccharide transport in Escherichia coli - Stefan U. Vetterli; Katja Zerbe; Maik Müller; Matthias Urfer; Milon Mondal; Shuangyan Wang; Kerstin Moehle; Oliver Zerbe; Alessandra Vitale; Gabriella Pessi; Leo Eberl; Bernd Wollscheid; et al. (2018)
Thanatin targets protein-protein interactions between LptA and LptD in the periplasmic bridge required for LPS transport.